Outcome of Fixed Dose of Radioiodine Therapy in Hyperthyroid Patients at NINMAS - Quddus, Sharmin; Begum, Fatima; Sultana, Nasreen; Perveen, Rahima; Mandal, Tapati; Islam, Urnas; Salekin, Mohammad Simoon; Sultana, Sadia; Nahar, Nurun (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: The modified fixed doses of radioactive iodine (RAI) in different types of hyperthyroidism had been practiced at National Institute of Nuclear Medicine & Allied Science (NINMAS) according to Society of Nuclear Medicine Bangladesh (SNMB) protocol since 2002 which was upgraded in 2015. The objective of the study was to observe the treatment outcome in modified fixed dose on previous protocol. Patients and Methods: In the present study the outcome of radioiodine therapy of hyperthyroid patients was retrospectively evaluated in 1349 consecutive primary hyperthyroid patients treated from January 2010 to December 2014 at NINMAS. Diagnosis of hyperthyroidism was done by thyroid function test; thyroid stimulating hormone (TSH), free triiodothyronine (FT3) & free thyroxine (FT4), 99m Technetium scan, thyroid radioiodine uptake and ultrasound imaging of thyroid gland. All patients received a fixed dose (8-29 m Ci) of radioactive iodine (RAI) depending on types of hyperthyroidism, visual assessment of gland size and severity of disease at diagnosis. They were followed up at 2 months of therapy, then every three months intervals for first year and thereafter 6 monthly up to 5 years or as needed during fluctuation of thyroid function. Results: Among the study population, 832 patients had diffuse toxic goiter (Graves’ disease), 369 patients were diagnosed as toxic multinodular goiter and 148 patients with single toxic nodule. At one year follow-up, permanent hypothyroidism occurred in 61.62% of patients and the cumulative incidence of hypothyroidism progressively increased up to 79.25% after 5 years. Cure or success of RAI therapy was considered as attainment of euthyroid state or hypothyroid state. About 11.26 % patients received more than single dose. Conclusion: Fixed dose RAI therapy is very much cost effective mode of treatment for primary hyperthyroidism with 89% success by giving single dose. Bangladesh J. Nuclear Med. 20(1): 37-40, January 2017